Devil rays (Chondrichthyes: Mobula) of the Arabian Seas, with a redescription of Mobula kuhlii (Valenciennes in Müller and Henle, 1841). Issue 1 (2nd May 2016) - di Sciara, Giuseppe Notarbartolo; Fernando, Daniel; Adnet, Sylvain; Cappetta, Henri; Jabado, Rima W.
Abstract: Devil rays (genus Mobula ) are pelagic elasmobranchs widely distributed throughout tropical, subtropical and warm‐temperate waters. Their occurrence and distribution remains poorly documented in the Arabian Seas region. A review is provided of species occurrence in these water bodies along with a synthesis of regional information on their biology and ecology. Based on the available evidence, five Mobula species occur in the region ( M . eregoodootenkee, M . japanica, M . kuhlii, M . tarapacana, and M . thurstoni ). Of these, three ( M . eregoodootenkee, M . tarapacana and M . thurstoni ) were found to occur in the Red Sea, and three ( M . eregoodootenkee, M . japanica, and M . kuhlii ) were found to occur in the Arabian/Persian Gulf. Mobula japanica and M . kuhlii are reported here for the first time in Gulf waters. All five species were found in the Indian Ocean waters between the Gulf of Aden and Pakistan. To address the still uncertain taxonomy of M . kuhlii, a redescription of this species is provided based on a sample of fresh specimen material. Mobula diabolus is a nomen ambiguum, never used to unambiguously designate any newly described species, and its use should be avoided. Considering the life‐history traits that make these species particularly vulnerable to fishing pressure, current levels of exploitation in by‐catch fisheries are unlikely to be sustainable, despite the fact that the trade in gill plates does not seem to be prevalent in this region. Critical knowledge gaps unfortunately still exist, crippling effective management and conservation actions. Copyright © 2016 John Wiley & Sons, Ltd.